Ethnobotanical study of medicinal plant species in Nensebo District, south-eastern Ethiopia - Girma, Zerihun; Abdela, Gemedi; Awas, Tesfaye (Ethnobotany Research and Applications, 2022)
Background: Plants are important sources of traditional medicine in many cultures. Ethiopia, being rich in floral and cultural diversity, merits documentation of medicinal plants and associated traditional medicinal knowledge in various parts of the country. To this end, an ethnobotanical study of medicinal plants was conducted in Nensebo district, southern Ethiopia. Methods: Ethnobotanical data were collected using semi-structured interviews, field guided walks, direct observation, focus group discussions and market surveys from December 2018 to February 2019. Both descriptive and quantitative methods were used for data analysis, as appropriate. Ethnobotanical data analysis techniques such as informant consensus factor, paired comparison, and preference ranking. Results: A total of 127 medicinal plant species belonging to 108 genera and 67 families were identified and documented. Medicinal plants were mostly (60%) collected from the wild. Of the recorded plant species, 70% were reported to be used to treat human ailments and 12% were used to treat livestock ailments. Herbs were the most frequently harvested medicinal plant growth form (32%). Among the plant parts used for medicine, leaves (36%) were the most frequently used. The most widely used mode of preparation for medicines was crushing (38%) and the most frequent route of administration was orally (31%). The most common human aliments treated in the area were gonorrhea, diarrhea, fever, tapeworm and headache, whereas the most common livestock aliments treated in the area were blackleg, cattle coughing, equine coughing, equine rheumatism. There was 21% informant consensus that Croton macrostachyus is effective in treating the common human aliment gonorrhea and also the preference raking findings indicated that Croton macrostachyus as most preferred medicinal plant species to treat gonorrhea. Conclusions: Several medicinal plant species and associated indigenous knowledge were reported to be used to treat human and livestock ailments, implying the local community depends on them for primary health care. As a result, there is a need for conservation of medicinal plants and associated indigenous knowledge in the area. Key words: Informants consensus, mode of preparation, pairwise comparison, route of administration